Graphical Models (San Diego, Academic Press, 2000)
Access available online from 2000- through ScienceDirect
Title from cover.
Keywords: Computer graphics -- Periodicals; Image processing -- Periodicals; Computer vision -- Periodicals; Grafische methoden; Digitale technieken; Beeldmanipulatie